Finite Element Analyses of Three Minimally Invasive Fixation Techniques for Treating Sanders Type II Intra‑Articular Calcaneal Fractures - Zhongmin Shi MD; Wenqi Gu (Foot & Ankle Orthopaedics)
Category: Hindfoot; Trauma Introduction/Purpose: Calcaneal Sanders type II or III fractures are highly disabling with significant burden. Surgical treatment modalities include open reduction and internal fixation (ORIF) techniques and a variety of minimally invasive surgical (MIS) approaches. ORIF techniques are associated with complications and traditional MIS techniques need extensive intraoperative fluoroscopic procedures. The present study aims to investigate the effects of three different minimally invasive internal fixation (MIIF) techniques used to treat Sanders type II intra-articular calcaneal fractures using finite element analyses. Methods: A 64-row spiral computed tomography scan was used to observe the calcaneus of a healthy adult. The scanning data were imported into Mimics in a DICOM format. Using a new model of a Sanders type II-B intra-articular calcaneal fracture, three minimally invasive techniques were simulated. Technique A involved fixation using an isolated minimally invasive locking plate; Technique B used a minimally invasive locking plate with one medial support screw; and Technique C simulated a screw fixation technique using four 4.0-mm screws. After simulating a 640-N load on the subtalar facet, the maximum displacement and von Mises stress of fragments and implants were recorded to evaluate the biomechanical stability of different fixation techniques using finite element analyses. Results: After stress loading, the maximum displacements of the fragments and implants were located at the sustentaculum tali and the tip of sustentaculum tali screw, respectively, in the three techniques; however, among the three techniques, Technique B had better results for displacement of both. The maximum von Mises stress on the fragments was < 56 Mpa, and stress on the implants using the three techniques was less than the yield strength, with Technique C having the least stress. Conclusion: All three techniques were successful in providing a stable fixation for Sanders type II intra-articular calcaneal fractures, while the minimally invasive calcaneal locking plate with medial support screw fixation approach exhibited greater stability, leading to improved enhancement for the facet fragment; however, screw fixation dispersed the stress more effectively than the other two techniques.